TRANSFORMASI VISUAL TOPENG BARONGAN DI DESA PANJER KECAMATAN PLOSOKLATEN KABUPATEN KEDIRI - Suryana, Wawan; Ali Rahim, Muhamad; Rakhmatdyanti, Nosy (Penerbit Lafadz Jaya, 2025)
Panjer Village is located in Plosoklaten District, Kediri Regency, famous for making barongan mask artwork made from wood waste and animal skin. The community lives together and holds fast to customs and traditions. In addition to making masks, they also work as farmers, plantation workers and construction workers as their livelihoods. The purpose of this study was to determine the visual expression of barongan artwork initiated from used goods (wood and leather waste). The research method used was a qualitative descriptive method. The results of this study indicate that the visual expression of the barongan mask has undergone a transformation in the form of shape, appearance, material, and coloring. This transformation is caused by innovation, artist creativity, progress in the era, as well as the socio-cultural environment and market demands.